POSITION OF TOURISM DESTINATION AREA DEVELOPMENT BASED ON TOURISM AREA CYCLE OF EVOLUTION TAMAN WISATA IMAN SITINJO - Rejeki Situmorang; Anwari Masatip; Marciella Elyanta (Asosiasi Dosen Muda Indonesia, 2022)
This study was aimed to analyze the position of the development tourist destination of Taman Wisata Iman Sitinjo at Dairi Regency. This research used descriptive qualitative research. The technique of data collection of this research was through observation, in-depth interviews, and documentation methods. The results of this study indicated that the position of developing tourist destinations in Taman Wisata Iman Sitinjo was in a stagnation position. In this phase, the challenges that will be faced by managers in the development of the Taman Wisata Iman Sitinjo were by creating new innovations, they are : (1) Involving local communities related to development in order to create new innovations, (2) Conducting trainings, seminars and meetings that can improve the quality of the performance of officers in service, (3) Identify or evaluate the performance of freelance daily workers, (4) Build and improve tourism facilities and infrastructure maintenance, (5) Organize new attractions both naturally, man-made and culturally, and (6) Creating a simple Internet Reservation System (IRS) to facilitate online checking, ordering and payment. It was concluded that the position of developing tourist destinations in the Taman Wisata Iman Sitinjo was in the stagnation stage based on the facts on the ground.